Wind profiles analysis near the ground - SADANI, LK (MAUSAM, 1987)
The present study describes the measurement of wind profile parameters in a winter month at Pune. The power index "a" has been calculated for different hours of the day in the lowest 3 metres. The average value of power index is found to be equal to 0.12, The values of frictional velocity u* and shear stress T are calculated from neutral wind profile, The horizontal mean wind speed shows increase in T at a reference height near the ground, In the evening (1900- 2020 hr) the atmospheric layers are found to be stably stratified.